The official guide to the new TOEFL iBT (McGraw-Hill, 2006)
TOEFL guide gives you: Everything you need to know about the new TOEFL® iBT, straight from the test-makers; Hundreds of authentic TOEFL iBT questions and essay topics - so you can study with the real thing; Companion audio CD with authentic TOEFL listening passages and sample responses to Speaking questions; In-depth descriptions of the multiple-choice Listening and Reading questions--with valuable tips for answering them; Detailed information about the Speaking and Writing sections, with scoring information, real student responses - and actual raters' comments; PLUS: Writer's Handbook for English Language Learners--to help you learn how to write essays in English.